Portable X-ray Fluorescence (pXRF) as a Tool for Environmental Characterisation and Management of Mining Wastes: Benefits and Limits - Nicolò Barago; Elena Pavoni; Federico Floreani; Matteo Crosera; Gianpiero Adami; Davide Lenaz; Francesca Larese Filon; Stefano Covelli (Applied Sciences, 2022)
Portable X-ray fluorescence (pXRF) is one of the main geochemical techniques employed in multi-elemental analysis screening for contaminated sites management. As the confidence of pXRF analyses are matrix-specific, efforts are made to provide studies of pXRF quality on different geochemical datasets, focusing on less investigated elements such as mercury (Hg) and antimony (Sb), to help both new and experienced users. The analysis of environmental solid samples from two decommissioned mining sites in NE Italy, characterised by Pb-Zn and (Hg-rich) Cu-Sb ore deposits, were prepared with two different protocols and compared with traditional destructive analyses. Sample composition was found strictly dependent to the occurrence of false positives and overestimation at low concentrations. In contrast, milling the sample did not produce major variations in the overall quality. Lead (Pb), Sb, and Zn reached the definitive data quality in at least one of the two datasets. Consequently, as far as a thorough QA/QC protocol is followed, pXRF can rapidly produce chemical data that is as accurate as that produced by destructive standard laboratory techniques, thus allowing to identify potential sources of contamination that could be reprocessed for the extraction of valuable elements and mitigating the dispersion of contaminants and ecological or health risks.